ACTA on Life Support: Why the Anti-Counterfeiting Trade Agreement is Failing and How Future Intellectual Property Treaties Might Avoid a Similar Fate - Alex Shepard (Washington University Global Studies Law Review, 2013)
ACTA is an agreement created outside the auspices of multilateral organizations and has been fraught with controversy since its initial talks in 2006, with criticism ranging from its negotiations lacking transparency, to its very existence merely being an initiative by rights holders to increase the international power of their intellectual property rights. Events in 2012 have created significant uncertainty as to the likelihood of the agreement coming into effect; the European Union parliament affirmatively declined to ratify it, and several European nations have refused to ratify ACTA in the wake of large protests. This Note is concerned with one particular criticism of ACTA: that despite its title and provisions for counterfeit goods, it is primarily a copyright treaty designed to respond to growing concerns of rights holders with respect to digital copyright infringement. Whether or not this criticism is valid, ACTA does contain several provisions relating to copyright infringement and piracy, both physical and digital, which are not present in prior IP treaties. And although the future of ACTA is far from certain (and likely far from bright), its goals within this sphere of intellectual property will not be interred along with it. Though the agreement may die, an autopsy could provide valuable information on trends in the development of IP treaties and how future treaties might avoid a similar fate.
Keywords: Anti-Counterfeiting Trade Agreement; ACTA; A.C.T.A.; IP; IP Treaties; Intellectual Property; Intellectual property treaties